1985
DOI: 10.1073/pnas.82.14.4688
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and kinetic cooperativity in ligand binding to multiple sites on a protein: Ca2+ activation of an ATP-driven Ca pump.

Abstract: Contrary to common belief, theoretical analysis does not predict-any necessary relationship between cooperativity in the equilibrium binding of an ion to multiple binding sites on a protein and cooperativity in the kinetic activation of a reaction for which such binding is prerequisite. The (5). Under these conditions, the conventional allosteric mechanism for generation of cooperativity can come into play, as illustrated by the cooperative association of oxygen with the four virtually identical and inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…In Figure 1, substrate ligation occurs in a random order, with the preferred pathway (or combination of pathways) being de-termined by the concentration of ATP and calcium. This type of ligation scheme has been proposed (Inesi et al, 1980;Tanford et al, 1985;Reynolds et al, 1985;Gould et al, 1986) to account for transient and steady-state kinetic measurements (Neet & Green, 1977;Inesi et al, 1980;Moller et al, 1980;Gould et al, 1986) involving substrate activation of the sarcoplasmic reticulum Ca 2+ -ATPase. The scheme in Figure 1 includes only steps that can be probed by varying calcium and ATP concentration on a steady-state time scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 1, substrate ligation occurs in a random order, with the preferred pathway (or combination of pathways) being de-termined by the concentration of ATP and calcium. This type of ligation scheme has been proposed (Inesi et al, 1980;Tanford et al, 1985;Reynolds et al, 1985;Gould et al, 1986) to account for transient and steady-state kinetic measurements (Neet & Green, 1977;Inesi et al, 1980;Moller et al, 1980;Gould et al, 1986) involving substrate activation of the sarcoplasmic reticulum Ca 2+ -ATPase. The scheme in Figure 1 includes only steps that can be probed by varying calcium and ATP concentration on a steady-state time scale.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrolytic cycle of the sarcoplasmic reticulum Ca 2+ -ATPase has been characterized as abbreviated in Figure 1 (De Meis & Vianna, 1979;Inesi et al, 1980;Tanford et al, 1985). Upon exposure to calcium and ATP, ligation of two calcium ions and ATP occurs in a random manner with the most favorable ligation sequence determined by the concentration of ligands.…”
mentioning
confidence: 99%
“…For the 1:1-per-ATP and 2:2-per-ATP models, the rate constants corresponding to the on and off binding of ATP, ADP, and P i are fixed and assumed equal to those reported by Tanford et al (37), as Brzezinski et al (6) and Weinstein (43) …”
Section: Discussionmentioning
confidence: 99%
“…Previously used rate and equilibrium constants, listed in the fourth column ofTable 1 in ref. 7, have been retained for the present analysis. These parameters quantitatively account for equilibrium Ca2+ binding to the pump protein at pH 7 and for kinetic activation of the pump reaction in leaky SR vesicles by ATP and cytoplasmic Ca2+, deviating from experimental data only in that the degree of cooperativity ofkinetic activation by Ca2+ is somewhat lower than most (but not all) investigators have reported.…”
mentioning
confidence: 99%
“…7, have been retained for the present analysis. These parameters quantitatively account for equilibrium Ca2+ binding to the pump protein at pH 7 and for kinetic activation of the pump reaction in leaky SR vesicles by ATP and cytoplasmic Ca2+, deviating from experimental data only in that the degree of cooperativity ofkinetic activation by Ca2+ is somewhat lower than most (but not all) investigators have reported. The second (loop f3), created by reaction step 1, permits the uncoupled leak of Ca2+ from high concentration in the SR into the cytoplasm, doing so by removing the restriction that the E2= E1 transition requires unoccupied Ca2+ binding sites.…”
mentioning
confidence: 99%